The native advertising advantage : build authentic content that revolutionizes digital marketing and drives revenue growth - Smith, Mike, 1966- (McGraw-Hill Education, 2017)
Gleaned from dozens of interviews with advertisers; marketers; software developers; journalists; and publishers; this book reveals why native advertising is an effective tool in any companys digital marketing strategyand how to use it to build new revenue streams. --